ANALISIS PROSES BERPIKIR SISWA DALAM MEMECAHKAN MASALAH MATEMATIKA DITINJAU DARI TIPE KEPRIBADIAN EXTROVERT-INTROVERT DAN GENDER - Hasanah, Nana; Mardiyana, Mardiyana; Sutrima, Sutrima (Jurnal Pembelajaran Matematika, 2013)
Abstract: This research aims to discribe the thinking process of male and female junior high school students with extrovert and introvert personality type in solving math problems using Polya steps. This research was a descriptive qualitative research. The subjects of this research were 10 junior high school students of 3 Depok Junior High School, consisting of 3 extrovert male students, 2 extrovert female students, 2 introvert male students, and 3 introvert female students. Subject selection procedure was done by purposive and snowball sampling methods. The data collection was conducted by categorizing studentsâ personality type, giving mathematics test to the research subjects, and interviewing the research subjects. In order to get valid data, the researcher used time triangulation. Technique of data analysis were done by: (1) classifying the data into four problem solving steps: (a) understand the problem, (b) make a plan, (c) carry out the plan, and (d) look back at the completed solution, (2) presenting the data in narrative text, and (3) concluding the thinking process of students in each problem solving steps. Male students with extrovert personality type, in understanding problem using assimilation thinking process, make a plan using assimilation thinking process, in carrying out the plan using accommodation thinking process, and look back the completed solution using assimilation thinking process. Female students with extrovert personality type, in understanding problem, make a plan, carry out the plan, and look back the completed solution using assimilation thinking process. Male students with introvert personality type, in understanding problem, make a plan, carry out the plan, and look back the completed solution using assimilation thinking process. Female students with introvert personality type, in understanding problem, make a plan, and looking back the completed solution using assimilation thinking process, and then in carry out the plan using incomplete assimilation thinking process.Keywords: Thinking Process, Problem Solving, Extrovert and Introvert Personality,Gender